PENAMBAHAN EKSTRAK JAHE MERAH DALAM PEMBUATAN MINUMAN BUBUK INSTAN BUAH BELIMBING - Anggita Yuni; Raswen Efendi; Evy Rossi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of the study was to identify the quality and the best formulation of instan starfruit powder with variation red ginger extract addition. The experiment research used a Completely Randomized Design (CRD), which consists of five treatments and three replications. The treatments were P1 (90 ml starfruit extract: 10 ml red ginger extract), P2 (80 ml starfruit extract: 20ml red ginger extract), P3 (70 ml starfruit extract: 30 ml red ginger extract), P4 (60 ml starfruit extract: 40 ml red ginger extract), and P5 (50 ml starfruit extract: 50 ml red ginger extract). Data were obtain using ANOVA and DNMRT at 5%. The result of this research showed that treatments given significant affect on total, sugar content, antioxidant content and organoleptic descriptive test on flavor and taste, but not significant  on water content, ash content and organoleptic descriptive test on. Colour and texture and also organoleptic hdonic text on colour, flavour, taste, texture and overall assesment. The best treatment were P1 (90 % starfruit extract : 10 % red ginger extract) with water content of 1,60 %, ash content 1,45 %, total sugar content 83,32 %, antioxydant content of 76,81 % µg/ml, with yellow brownish, rather flavoeful red ginger and starfruit, rather taste red ginger and starfruit, rather texture soft and panelist prefered the instant powder starfruit.Keywords: Instant powder, starfruit, red ginger